2019
DOI: 10.1016/j.nicl.2019.101746
|View full text |Cite
|
Sign up to set email alerts
|

High serum high-density lipoprotein-cholesterol is associated with memory function and gyrification of insular and frontal opercular cortex in an elderly memory-clinic population

Abstract: The issue of whether serum lipid marker values are cognitively and neurologically significant for elderly individuals attending a memory clinic has been controversial. We investigated the associations of serum lipid markers with the memory function and cortical structure in 52 patients aged ≥75 years who had attended our memory clinic based on their subjective memory complaints. None had a history of medication for hyperlipidemia. The Wechsler Memory Scale-Revised (WMS-R) was administered to all patients for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…Underlying neural mechanism of the relationship between cholesterol levels and cognitive performance/decline has not been well established. While studies have generally agreed that high HDL levels might be beneficial to brain health (Wolf et al, 2004;Ward et al, 2010;Armstrong et al, 2019;Kinno et al, 2019), the relationship between hTC/LDL levels and brain function/structure remains controversial; both negative (Whalley et al, 2003;Reiman et al, 2010;Qiu et al, 2012;Williams et al, 2013) and positive (Leritz et al, 2011;Aine et al, 2014;Coutinho et al, 2017;Chung et al, 2018) relationships have been identified, even in the same sample (Zhang et al, 2016). In the present study, we provided evidence suggesting low-normal TC (TC < 160 mg/dl) is associated with reduced GMv in medial temporal regions (including bilateral anterior HIP).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Underlying neural mechanism of the relationship between cholesterol levels and cognitive performance/decline has not been well established. While studies have generally agreed that high HDL levels might be beneficial to brain health (Wolf et al, 2004;Ward et al, 2010;Armstrong et al, 2019;Kinno et al, 2019), the relationship between hTC/LDL levels and brain function/structure remains controversial; both negative (Whalley et al, 2003;Reiman et al, 2010;Qiu et al, 2012;Williams et al, 2013) and positive (Leritz et al, 2011;Aine et al, 2014;Coutinho et al, 2017;Chung et al, 2018) relationships have been identified, even in the same sample (Zhang et al, 2016). In the present study, we provided evidence suggesting low-normal TC (TC < 160 mg/dl) is associated with reduced GMv in medial temporal regions (including bilateral anterior HIP).…”
Section: Discussionmentioning
confidence: 50%
“…In another study involving healthy older controls and individuals with mild cognitive impairment (MCI) or AD, low HDL was associated with low hippocampal volume (Wolf et al, 2004). In a very recent study with older adults (75 years old or older) who had subjective memory complaints, HDL was positively correlated with memory performance and gyrification indices of bilateral insular and frontal opercular cortices (Kinno et al, 2019). In a large longitudinal cohort study, higher HDL levels were associated with less steep GMv decline in the entorhinal cortex and parahippocampal gyrus, as well as a lower risk of future cognitive impairment (Armstrong et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…A recent structural MRI study demonstrated that gray matter reduction in the parietal, occipital, and cerebellar areas associated with increased serum TG and LDL-C in subjects with obesity [ 14 ]. Using surface-based morphometry analysis, Kinno et al identified positive correlations between serum HDL-C level and gyrification indices of the insular and frontal opercular cortices in an elderly memory-clinic population [ 5 ]. Collectively, these prior reports point towards a negative effect of serum TC, TG, and LDL-C yet a protective effect of HDL-C on brain function and structure.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is now emerging that serum lipid profile is linked to many aspects of human cognition. A large number of cross-sectional studies have established that higher serum levels of total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) are associated with poorer cognitive performance in multiple domains (e.g., working memory, recognition memory, executive control, sustained attention, and inhibitory processing) [ 1 5 ], whereas higher serum high-density lipoprotein cholesterol (HDL-C) level is related to better cognitive functions such as verbal learning, memory, and executive function [ 5 7 ]. These associations are also confirmed by longitudinal studies consistently suggesting that elevated TC, TG, and LDL-C in midlife are predictive of greater cognitive decline in late life while higher HDL-C predicts better maintenance of cognitive function [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation